2019
DOI: 10.1177/2043808719838937
|View full text |Cite
|
Sign up to set email alerts
|

Greater body appreciation moderates the association between maladaptive attentional biases and body dissatisfaction in undergraduate women

Abstract: Attentional biases for weight-related information are thought to contribute to maintenance of body dissatisfaction and eating disorders. Women with greater body appreciation may pay less attention to thinideal cues if body appreciation protects them from negative effects of thin-ideal media, and if so, they may be less susceptible to development of maladaptive attentional biases. The present study used eye-gaze tracking to measure attention to weight-related words/images in 167 body-dissatisfied undergraduate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 47 publications
1
18
2
Order By: Relevance
“…The dot probe task has previously been shown to have poor internal consistency and test-retest reliability [55,[65][66][67], which may explain why studies using the dot probe task report inconsistent results for the relationship between body dissatisfaction and attentional bias towards low fat bodies. In contrast, studies using eye-tracking measures consistently report a positive relationship [16][17][18][19]. Given the poor reliability of the dot probe task as a measure of attentional bias, we should interpret our results for ΔAB with caution.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The dot probe task has previously been shown to have poor internal consistency and test-retest reliability [55,[65][66][67], which may explain why studies using the dot probe task report inconsistent results for the relationship between body dissatisfaction and attentional bias towards low fat bodies. In contrast, studies using eye-tracking measures consistently report a positive relationship [16][17][18][19]. Given the poor reliability of the dot probe task as a measure of attentional bias, we should interpret our results for ΔAB with caution.…”
Section: Discussioncontrasting
confidence: 58%
“…Body size adaptation is also indirectly related to body dissatisfaction, with this relationship being mediated by visual attention. Eye-tracking [16][17][18][19] and reaction time [20][21][22] studies show that people with high body dissatisfaction direct more attention towards low fat body stimuli than people with low body dissatisfaction. Further, Stephen and colleagues demonstrated that people adapt to the body size they direct more attention towards.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of an association also contrasts with studies using eye-tracking as a measure of attentional bias (e.g. Stephen et al, 2018;Tobin et al, 2019).…”
Section: Discussionmentioning
confidence: 57%
“…Skinner et al, 2018) and have consistently produced evidence for a relationship between body dissatisfaction and attentional bias to thin bodies (e.g. Stephen et al, 2018;Tobin et al, 2019). Therefore, future research may employ eye-tracking techniques to investigate the moderating effects of ethnicity and ethnicity-congruency on the relationship between body dissatisfaction and attentional bias to body size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation